COGNITIVE DEVELOPMENT IN EARLY CHILDHOOD: ANALYZING THE IMPACT OF PARENTAL INTERACTION AND EDUCATIONAL ENVIRONMENT - Sirjon; Diana Setyaningsih; Elyaum Farihah (World Psychology, 2026)
Early childhood represents a critical period for cognitive development, during which foundational abilities such as language, memory, and problem solving are rapidly formed through interaction with the surrounding environment. Parental interaction and educational environment are recognized as influential factors, yet their combined effects are examined separately. This study aims to analyze the impact of parental interaction and educational environment on cognitive development in early childhood using an analytical perspective. A correlational research design was employed involving children aged four to six years enrolled in early childhood education institutions and their parents. Data were collected through parental interaction questionnaires, educational environment assessments, and standardized cognitive development tests, then analyzed using descriptive statistics, correlation, and multiple regression techniques. The results indicate that both parental interaction and educational environment have positive relationships with early childhood cognitive development, with parental interaction emerging as a stronger predictor. The combined model explains variance in cognitive development outcomes, demonstrating complementary roles of home and school contexts. The findings suggest that cognitive development in early childhood is shaped by cumulative aligned experiences across family and educational settings. Strengthening parental engagement alongside improving early educational environments is essential for optimizing cognitive development during this formative stage for young children.